2014
DOI: 10.1016/j.gexplo.2014.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Soil contamination near a former Zn–Pb ore-treatment plant: Evaluation of deterministic factors and spatial structures at the landscape scale

Abstract: Historical soil contamination within a 3 km radius of a former ore treatment plant was evaluated. A total of 247 topsoil samples were collected in a stratified random sampling design taking into account three factors: land use (LU), soil type (ST) and wind direction (WD). Concentrations of trace elements (Cd, Co, Cr, Cu, Ni, Pb and Zn) and major elements (Ca, Mg, K, Fe, Al, Mn) as well as various soil properties (pH water , pH KCl , TOC and N) were measured. Total Cd, Pb and Zn concentrations were higher than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 24 publications
0
17
0
2
Order By: Relevance
“…The high contents of As, Co, Cu, Fe, Mo, Ni, and V in Tailings and topsoil in the Near area in relation to those detected in the local baseline clearly indicate contamination by fallout dust coming from the ore processing plants and tailings piles. Liénard et al (2014) concluded that severe contamination of topsoil by Cd, Cu, Pb, and Zn within a 3-km radius circle surrounding stacks of a former Zn-Pb ore treatment plant of the Sclaigneaux calaminary site in Belgium is probably driven by anthropogenic factors, specifically historical industrial activities and subsequent atmospheric deposition. Li et al (2015) also reported that Pb/Zn smelting and resulting dust fallout have led to significant contamination of the local topsoil by Zn, Pb, Cd, As, Sb, and Hg in a town in Yunnan Province of China.…”
Section: Resultsmentioning
confidence: 99%
“…The high contents of As, Co, Cu, Fe, Mo, Ni, and V in Tailings and topsoil in the Near area in relation to those detected in the local baseline clearly indicate contamination by fallout dust coming from the ore processing plants and tailings piles. Liénard et al (2014) concluded that severe contamination of topsoil by Cd, Cu, Pb, and Zn within a 3-km radius circle surrounding stacks of a former Zn-Pb ore treatment plant of the Sclaigneaux calaminary site in Belgium is probably driven by anthropogenic factors, specifically historical industrial activities and subsequent atmospheric deposition. Li et al (2015) also reported that Pb/Zn smelting and resulting dust fallout have led to significant contamination of the local topsoil by Zn, Pb, Cd, As, Sb, and Hg in a town in Yunnan Province of China.…”
Section: Resultsmentioning
confidence: 99%
“…Adsorption of heavy metals is also highly dependent on soil components that include silicate clays, organic matter, iron, aluminium, and manganese oxides [44,45]. The soil contents of Cd, Pb, and Ni are variable (e.g., northern Pakistan, southwestern China, Wallonia region of Belgium, and northwest of Iran: Cd 0.08-4.5, Pb 17.0-672.0, and Ni 0.46-103.0 mg kg −1 soil) depending on agroclimatic conditions [27,[46][47][48].…”
Section: Resultsmentioning
confidence: 99%
“…Aluminum was selected to be the reference value. Indeed, Al is the most common reference value used to calculate the EF (e.g., Bourennane et al, 2010;Liénard et al, 2014).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%